High Expression of PAMR1 Predicts Favorable Prognosis and Inhibits Proliferation, Invasion, and Migration in Cervical Cancer - Yang, Rui; Ma, Mingjun; Yu, Sihui; Li, Xi; Zhang, Jiawen; Wu, Sufang (Frontiers in Oncology, 2021)
Peptidase domain containing associated with muscle regeneration 1 (PAMR1) is frequently lost in breast cancer samples and is considered as a tumor suppressor. The roles and mechanisms of PAMR1 in other types of cancers are still unclear. In our present study, we identified PAMR1 as an invasion-related regulator in cervical cancer. Public database and immunohistochemical (IHC) analysis showed that the expression level of PAMR1 in cervical cancer tissues was lower than that in normal cervix tissues, and was negative related to the clinicopathologic features. High expression of PAMR1 also predicted a better prognosis of cervical cancer patients. CCK8, Transwell and wound healing assays demonstrated that knockdown of PAMR1 facilitated proliferation, migration and invasion of cervical cancer cells. Additionally, Gene Set Enrichment Analysis (GSEA) showed a variety of cancer-related pathways potentially activated or suppressed by PAMR1. Moreover, we verified that PAMR1 inhibited Myc targets and mTORC1 signaling pathway. In conclusion, our study revealed the suppressor role of PAMR1 in cervical cancer, providing a new insight into the molecular mechanism of cervical cancer progression.